Effectiveness of artesunate–amodiaquine vs. artemether–lumefantrine for the treatment of uncomplicated falciparum malaria in Nanoro, Burkina Faso: a non‐inferiority randomised trial. Issue 4 (5th February 2014) - Tinto, Halidou; Diallo, Salou; Zongo, Issaka; Guiraud, Issa; Valea, Innocent; Kazienga, Adama; Kpoda, Hervé; Sorgho, Hermann; Ouédraogo, Jean‐Bosco; Guiguemdé, Tinga Robert; D'Alessandro, Umberto
Abstract Objectives Artemisinin‐based combination therapies (ACTs) are essential for the effective control of falciparum malaria in endemic countries. However, in most countries, such choice has been carried out without knowing their effectiveness when deployed in real‐life conditions, that is, when treatment is not directly observed. We report here the results of a study assessing the effectiveness of the two ACTs currently recommended in Burkina Faso for the treatment of uncomplicated malaria, that is, artemether–lumefantrine (AL) and artesunate–amodiaquine (ASAQ). Methods Between September 2008 and January 2010, 340 children were randomised to one of the two study arms and followed up for 42 days. Treatment was administered according to routine practices, that is, the first dose was given by study nurses who explained to the parent/guardian how to administer the other doses at home during the following 2 days. Results The results showed a significantly higher unadjusted adequate clinical and parasitological response in the ASAQ (58.4%) than in the AL arm (46.1%) at day 28 but these trends were similar after correction with PCR data (ASAQ (89.7%) and AL (89.8%)). New infections started to appear after day 14, first in the AL and then in the ASAQ arm but at day 42 day of follow‐up we observed no difference in the occurrence of recrudescent infection. Conclusion Despite a lower cure rate than those reported in efficacy studies in which the treatment administration was directly observed, both AL and ASAQ can still be used for the treatment of uncomplicated malaria in Burkina Faso.